Acupuncture Therapy Combined with Cucumber Juice (Cucumis Sativus) Reduces Blood Pressure in Hypertension - Robby Insani Hasan; Kurnia Eka Putri; Suwaji Handaru Wardoyo (Poltekkes Kemenkes Surakarta, 2023)
Background: Hypertension is a condition of elevated arterial blood pressure that can cause dysfunction of vital organs such as the heart and kidneys. Complementary therapies, such as acupuncture and consumption of cucumber juice, are known to help lower blood pressure. This study aims to determine the effect of acupuncture therapy combined with cucumber juice on blood pressure in hypertensive patients. Methods: This study used a true experimental design with a pretest-post test control group design. The sampling technique used purposive sampling with a sample size of 36 hypertensive patients at the BMI Pringsewu Lampung Primary Clinic who met the inclusion and exclusion criteria. The research instruments used observation sheets and blood pressure measurements with an aneroid sphygmomanometer and stethoscope. Data analysis was performed using univariate and bivariate analysis with the One-Way ANOVA test. Results: The greatest average decrease in systolic blood pressure occurred in the acupuncture therapy group combined with cucumber juice, with a percentage decrease of 13.76% in systolic and 11.10% in diastolic blood pressure. The results of the analysis showed a significant effect on the reduction in systolic blood pressure (F = 6.369; p = 0.005), while the reduction in diastolic blood pressure was not significant (p = 0.205). Conclusion: Acupuncture therapy combined with cucumber juice is effective in lowering systolic blood pressure in hypertensive patients. This combination therapy can be used as a non-pharmacological complementary alternative for controlling hypertension.